2014
DOI: 10.11648/j.ijnfs.20140306.19
|View full text |Cite
|
Sign up to set email alerts
|

Production and Quality Assessment of Functional Yoghurt Enriched with Coconut

Abstract: Abstract:The potential of producing acceptable symbiotic yoghurt enriched with coconut-cake was investigated. Yoghurt samples A (Control), B, C and D were produced at 0%, 10%, 20%, and 30% of milk substitutions with coconut-cake. The physico-chemical, microbial and sensory analyses were determined to ascertain the quality attributes of the products. The results of physico-chemical analysis obtained showed increase in values for pH (4.32-4.45), specific gravity (1.03-1.14), soluble solids (7.10-10.47%) and swee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 31 publications
3
21
1
3
Order By: Relevance
“…This variation could be due to the different climatic conditions of growth as well as the degree of drying applied by the farmers. Sample CEY0 had the highest moisture content of 81.95%, which fell within the range of most yoghurts available in the market (80-86%) [15]. The moisture content for all the enriched samples was significantly lower than that of CEY0 and the variance between them was dependent on the quantity of chia seeds used in the formulation.…”
Section: Proximate Composition and Calorific Value Analysismentioning
confidence: 74%
“…This variation could be due to the different climatic conditions of growth as well as the degree of drying applied by the farmers. Sample CEY0 had the highest moisture content of 81.95%, which fell within the range of most yoghurts available in the market (80-86%) [15]. The moisture content for all the enriched samples was significantly lower than that of CEY0 and the variance between them was dependent on the quantity of chia seeds used in the formulation.…”
Section: Proximate Composition and Calorific Value Analysismentioning
confidence: 74%
“…The addition of flavour not only gives a wide array of tastes but also increases the sweetness of yoghurt (Weerathilake et al, 2014). Ndife et al (2014) reported that fat content has a considerable impact on both instrumental and sensory characteristics of yoghurts. The reason for this fact is that fat has better rheology and it acts as an aroma solvent compared to skimmed and low-fat yoghurt.…”
Section: Resultsmentioning
confidence: 99%
“…However, among these volatile compounds, acetaldehyde is the major flavour compound of yoghurt which gives pleasant, fresh and fruity aroma. The low flavour values could be due to the high content of carbohydrate which increases the sweetness of yoghurt (Ndife et al, 2014;Corrieu and Beal, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations